Epilepsy and COVID-19: challenges for the neurologist, patient, and national health system during a pandemic - M. Vaišvilas; A. Jasionis; R. Mameniškienė (Neurologijos seminarai)
Although COVID-19 is most often associated with respiratory symptoms and less frequent multiple organ failure, a variety of neurological symptoms is possible in infected individuals. Cases of COVID-19-induced seizures have been reported, although their association with epilepsy is questionable. When a person with epilepsy is infected with COVID-19 and treated with antiviral drugs, the interaction of these drugs with antiepileptic drugs used is important. The psychological condition of patients is an important factor in controlling seizures, and the pandemic changes the care of patients with chronic diseases. In this article, we provide a review of the literature on the treatment of symptomatic seizures and status epilepticus, and the care of people with epilepsy during the COVID-19 pandemic. We also present the latest recommendations for electroencephalography.